Indonesia Pengaruh Reputasi Auditor, Fee Audit, Opini Audit dan Ukuran Perusahaan Terhadap Audit Delay : (Studi Empiris pada Perusahaan Manufaktur Sektor Aneka Industri yang terdaftar di Bursa Efek Indonesia Tahun 2021-2023) - Resti Lisa Utami (Jurnal Literasi Akuntansi, 2025)
Purpose: This study aims to determine: (1) whether Auditor Reputation has an effect on Audit Delay in manufacturing companies in various industrial sectors listed on the IDX in 2021-2023 (2) whether Audit Fee has an effect on Audit Delay in manufacturing companies in various industrial sectors listed on the IDX in 2021-2023 (3) whether Audit Opinion has an effect on Audit Delay in manufacturing companies in various industrial sectors listed on the IDX in 2021-2023 (4) whether Company Size has an effect on Audit Delay in manufacturing companies in various industrial sectors listed on the IDX in 2021-2023. Method: This type of research is quantitative research using secondary data. Sampling using purposive sampling technique. The sample consists of 75 data from 25 manufacturing companies in various industrial sectors listed on the Indonesia Stock Exchange in 2021-2023. The data analysis technique used is quantitative analysis using Eviews. Finding: Based on the research results, it shows that auditor reputation does not affect audit delay, audit fees affect audit delay, audit opinion affects audit delay and company size affects audit delay. Novelty: This study adds the audit fee variable as one of the factors influencing audit delay, where this variable has never been studied in previous studies.